2016
DOI: 10.7748/mhp.2016.e1133
|View full text |Cite
|
Sign up to set email alerts
|

‘Give us something to do’: reflections on running a group therapy programme

Abstract: People on inpatient psychiatric wards often report feeling bored, and say that they would like access to therapy groups on the ward to help aid their recovery. However, there are many challenges to providing groups on wards, including lack of staff with the requisite time and expertise. This paper describes how a therapy group programme was designed and implemented on a psychiatric triage ward. The group programme was psychology-led, with involvement from the nursing team as cofacilitators. Challenges and oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The most frequently reported barrier related to the nature of the inpatient environment and care delivery, which was highlighted in 14 out of 16 studies. The most common obstacle was a lack of time that staff had to deliver psychological therapy, which was most frequent when psychological therapies were being delivered by non‐psychological staff (Chang et al, 2014; Folke et al, 2015; Jacobsen & Clark, 2016). The wards are inherently busy, staff members have other responsibilities to attend to and service users have other appointments (Fife et al, 2019; Tyrberg et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most frequently reported barrier related to the nature of the inpatient environment and care delivery, which was highlighted in 14 out of 16 studies. The most common obstacle was a lack of time that staff had to deliver psychological therapy, which was most frequent when psychological therapies were being delivered by non‐psychological staff (Chang et al, 2014; Folke et al, 2015; Jacobsen & Clark, 2016). The wards are inherently busy, staff members have other responsibilities to attend to and service users have other appointments (Fife et al, 2019; Tyrberg et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The studies outlined that not all multidisciplinary team members were appropriately trained or had the confidence to use therapeutic approaches (Folke et al, 2015; Jacobsen & Clark, 2016; Small et al, 2018). The sessions were also not delivered routinely because of persistent operational challenges such as staff sickness, unplanned leave and unpredictable rotas (Jacobsen & Clark, 2016; Paterson et al, 2019; Gaudiano et al, 2020). The articles also suggested that some nursing staff did not feel running therapeutic groups was appropriate for their role (Moore et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations